PENGUKURAN DAN PEMETAAN KADASTRAL DENGAN METODE IDENTIFIKASI PETA FOTO - Bambang Sudarsono; Arief Laila Nugraha (Diponegoro University, 2008)
To justify the law enforcement in the land’s ownership right, Government of Indonesia (GOI) hasestablished land registration program in all Indonesian territory that refers to the regulation. This landregistration program consists from several action which is, surveying, mapping, and land documentation.Land surveying should be refers to the cadastral technical rule and jurisdiction rule. Land surveying withphoto map identification could be applied by using photo map as base map registration. To verify the landboundaries in the field we must get an agreement from the land’s owner, neighbours, local governmentofficer and surveyor. Land surveying that use identification method should be refers to the technicalspecification order from Badan Pertanahan Nasional (BPN). There are several limitations from theidentification method; we can’t carry out this method in the crowd residence area and area which coveredby trees.